Action, action, action : the early cinema of Raoul Walsh - Conley, Tom (State University of New York Press, 2022)
"Studies the force of action, motion, and vision in the early cinema of Hollywood director Raoul Walsh"-- Provided by publisher
Keywords: Walsh, Raoul, -- 1887-1980 -- Criticism and interpretation.; Walsh, Raoul, -- 1887-1980; Motion pictures -- History -- 20th century.; Motion picture producers and directors -- United States -- Biography.; Cinéma -- Histoire -- 20e siècle.; Producteurs et réalisateurs de cinéma -- États-Unis -- Biographies.; PERFORMING ARTS / Film & Video / History & Criticism.; Motion picture producers and directors; Motion pictures; United States; 1900-1999; Biographies; Criticism, interpretation, etc.; History; Biographies.